Chondrosarcoma of the Thyroid Cartilage Successfully Treated With Partial Resection of the Thyroid Cartilage - Fedorová, Katarína; Zeleník, Karol; Formánek, Martin; Židlík, Vladimír; Komínek, Pavel (Ear, nose, & throat journal, 2023)
Chondrosarcoma of the thyroid cartilage is a sporadic disease with nonspecific clinical presentation. Smooth swelling of the supraglottic area should arouse suspicion of possible pathology. In addition to laryngoceles, which usually do not have a significant impact, otolaryngologists should consider chondrosarcoma of the thyroid cartilage and indicate computed tomography (CT). Late diagnosis leads to worse prognosis, particularly worse voice after more extensive surgery, need for tracheostomy, and worse survival from higher degree chondrosarcomas.
Keywords: Laryngectomy; Thyroid Cartilage; chondrosarkom; tyreoidální chrupavka; Humans; nádory hrtanu; Laryngocele; laryngocele; Chondrosarcoma; Laryngeal Neoplasms; laryngektomie; lidé